Lean Supply Chain Ecosystem for MSME a Framework for Phased Implementation. (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
Supply Chain Management is the major operation tool for all the Industries. Micro, Small and Medium Industries are aware of the supply chain management but many of these companies have not yet followed this operation tool. In this scenario the Lean Supply Chain Management is also a part of the supply chain management, it means that how to minimize the supply chain cost and to use effectively without changing the time as well as reduce the time to deliver also.  Based on the literature and Industry visit there are some gaps identified which affect the supply chain management and how it to be change into the Lean Supply Chain Management there are Communication, Information Sharing System, Cost control planning, Customer service, Industry trends, Customer linkages, Service philosophy, Seasonality Management Mindset, Lean Supply chain problem readiness, Supplier base, Data infrastructure Distribution center swaps and Lean Supply chain bottlenecks intervention. When the industry were fill this gaps the Supply Chain Management is to convert into the Lean supply Chain Management through this Micro, Small and Medium Industries can make their business well profitable and comfortable.